CORRELATION OF USING CONTRACEPTION WITH BREAST MILK PRODUCTION IN BREASTFEEDING MOTHERS IN THE ANDALAS PUBLIC HEALTH CENTER IN PADANG - Rahmayanti, Rini; Yolanda, Yola (Saintika Medika: Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2019)
Indonesia is still categorized as low in 2017, only 35.73% with a target of 50%. West Sumatra Province occupies the fifth position with exclusive breastfeeding coverage of 73.6%. The percentage of babies with exclusive breastfeeding in the city of Padang in 2017 was 74.77% of the target of 80%. Andalas Puskesmas has the lowest exclusive breastfeeding coverage of 59.84%. The purpose of this study was to determine the relationship between hormonal contraceptive use and breast milk production in breastfeeding mothers in the Kubu Village in the Parak Karakah Work Area of the Andalas Padang Health Center in 2019. This type of research was analytic with a cross sectional design. The population of mothers who have babies aged 1-6 months is 268 people with a sample of 73 people. Purposive sampling technique. Analyzed univariately using a frequency distribution table and bivariate using the Chi-Square statistical test. Univariate analysis results showed there were more than half (57.5%) with insufficient milk production. More than half (67.1%) use hormonal birth control. The results of bivariate analysis have a relationship between the use of hormonal contraception with the production of breast milk (X2h> X2t). The conclusion is that there is a relationship between hormonal contraceptive use factors, and milk production. It is expected that health workers can provide counseling to nursing mothers by providing health education about efforts to increase milk production.